PEDAGOGICAL AND DIDACTIC CONDITIONS OF FORMATION OF INDEPENDENT THINKING SKILLS IN READING LITERACY - Mahfuza Urinova (Innovate Conferences, 2025)
This article analyzes the pedagogical and didactic conditions of developing independent thinking skills in the process of forming reading literacy among elementary school pupils. Also, special attention is paid to the role of the teacher in increasing the creative activity of pupils, developing critical thinking and forming the ability to make independent decisions.
Keywords: independent thinking, pedagogical conditions, didactic conditions, educational process, reading literacy, teaching methods.